A Tripartite Model of Community Attitudes to Palliative Care. (October 2019) - O'Connor, Moira; Breen, Lauren J.; Watts, Kaaren J.; James, Henry; Goodridge, Rhys
Background: Despite a growth in palliative care services, access and referral patterns are inconsistent and only a minority of people who would benefit from such care receive it. Use of palliative care is also affected by community attitudes toward palliative care. As such, determining community attitudes toward palliative care is crucial. We also need to determine what predicts attitudes in order to provide appropriate information and education. Objectives: The 2 research questions were: (1) What are community attitudes toward palliative care? and (2) what are the determinants of community attitudes toward palliative care? Design: A tripartite model of attitudes was used, which articulates attitudes as comprising knowledge and experience, emotions, and beliefs. A cross-sectional descriptive survey was used. Participants: A community sample of 180 participants completed the survey. Results: The average attitude and belief responses were very positive, the average emotions responses were somewhat positive. The sample had good knowledge of palliative care. Lowest knowledge scores were reported for the items: "Euthanasia is not part of palliative care, " "Palliative care does not prolong or shorten life, " and "Specialist palliative care is only available in hospitals." After controlling place of birth and age, it was found that beliefs, emotions, and knowledge each accounted for a significant proportion of unique variance in attitude toward palliative care. Each variable had a positive relationship with attitude. Conclusion: Beliefs, emotions, and knowledge all need to be incorporated into palliative care community education programs.